If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(12x + 6) + 19 = 0 Reorder the terms: 2(6 + 12x) + 19 = 0 (6 * 2 + 12x * 2) + 19 = 0 (12 + 24x) + 19 = 0 Reorder the terms: 12 + 19 + 24x = 0 Combine like terms: 12 + 19 = 31 31 + 24x = 0 Solving 31 + 24x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-31' to each side of the equation. 31 + -31 + 24x = 0 + -31 Combine like terms: 31 + -31 = 0 0 + 24x = 0 + -31 24x = 0 + -31 Combine like terms: 0 + -31 = -31 24x = -31 Divide each side by '24'. x = -1.291666667 Simplifying x = -1.291666667
| -5-(t/5)-9 | | 36=-1/2x=16 | | 26+6x+20=46+10x | | 4y-7=y+1 | | 2/7(x-9)=-5 | | .01x=-.01 | | 21+7w=12+6w | | 5*n=3000 | | 16x-1/2=36 | | s+5=6+2 | | y/n-3=11 | | x/.3=-.8 | | 5*2=9*5 | | 1.33x=7 | | b^2+8b-70=0 | | 89/3 | | 4x+8=4x+24 | | 1.43x=x+3 | | (7x-2)-(2x+8)=3x+14 | | 45*75-76x(y+45)-76= | | 1+(-2x)+5=4x+(-3) | | 7t^2-6=0 | | 4y-11=0 | | x=x^2-5x-36 | | z+12=x+6 | | 73+x=d | | f(x)=(x-2)(x+3)(x-5) | | 6x-(5x-5)=-8-2(x+12) | | 5*2=9-1 | | -4c+8=-4c+8 | | 5(2x+6)-2x=8(x+5) | | -4/17(17/8) |